A STUDY ON CLINICAL EVALUATION AND PRESCRIBING PATTER OF DRUGS USED IN SCHIZOPHRENIA PATIENTS (Pharmacology & Toxicology Research (ISSN 2349-4581), 2024)
The prospective observational study conducted at Swasthik Samalochana Hospital, Warangal during February2013-July 2013. The study enrolled 150 in-patients and out-patients with Schizophrenia were included in the study who met inclusion criteria, after obtaining their informed consent. In 150 Patients in the Psychiatry clinic were characterized into based on  predo-minant symptoms abnormal behavior, Hallucinations. In Psych-ological patients 51% males and 48% females were suffering schizophrenia  diso-rder and various causes are 43.3% of family history, 12.6% of alcoholic, 6.6% family problems, 7.3% of thyroid disorders, 1.3% of post-menopa-  usal problems. In this study nearly 50% of the patients had 3 risk factors primarily like family history, alcohol, financial problems. The necessity of patient counseling by a clinical pharmacist plays a major role in  educat-ional interventions and healthy life style modifications were an essential part in the prevention of schizophrenia and different psychological diso-rders of central nervous system. Abnormal behaviour, hallucinations and aggressive are the most predominant symptoms in this study.